The Analysis of Science Process Skills (SPS) of 11th Grade Science Students - Elvy Rahmi Mawarnis; Ilham Akbar; Mimi Herman (Hydrogen: Jurnal Kependidikan Kimia, 2023)
This research is motivated by students who do not understand chemistry lessons, especially in explaining formulas and calculations. Even though the learning methods and models used by teachers are different so that students have a "mindset" that learning chemistry is a difficult subject to understand. Another problem experienced by the teacher during learning, only the teacher is actively involved during learning while students are more dominant in listening to the teacher's explanation. The purpose of this study was to analyze and find out the Science Process Skills (SPS) of 11th grade science students at SMAN 1 Pulau Punjung. This research method is qualitative (descriptive). The subject of this research was the class of Stage F.2 which consisted of 27 students. Data collection techniques in this study were observation techniques, interview questionnaires, SPS documentation and questionnaires.  The data obtained relates to the science process skills of students. Furthermore, researchers used data analysis techniques, namely the theory of Miles and Huberman which included data reduction, data presentation, and data verification and drawing conclusions, then the data was validated using the triangulation method. Based on the research that has been done, it can be interpreted that the results of the SPS analysis of Phase F.2 students of SMAN 1 Pulau Punjung on the observation indicator with a proportion of 89% and the experimental design indicator with a proportion of 82% both have very good categories. Then a classification indicator with a proportion of 77% and a predictive indicator with a proportion of 68% both have good categories. Then for the hypothesis delivery indicator with a percentage of 58% it is categorized as enough while for the hypothesis preparation indicator it has a proportion of 39% in the not enough category.